The Appropriateness of Surveillance Colonoscopy Intervals after Polypectomy - Eline Schreuders; Jerome Sint Nicolaas; Vincent de Jonge; Harmke van Kooten; Isaac Soo; Daniel Sadowski; Clarence Wong; Monique E van Leerdam; Ernst J Kuipers; Sander JO Veldhuyzen van Zanten (Canadian Journal of Gastroenterology)
BACKGROUND: Adherence to surveillance colonoscopy guidelines is important to prevent colorectal cancer (CRC) and unnecessary workload.